Comparison of Knowledge, Attitude and Practice Regarding Usage of Mobiles During Driving amongst Medical and Engineering Students Aged 18-21 Years in Bengaluru North (Medico Legal Update, 2021)
WHO categorizes driver distraction like mobile usage as an important risk factor for road crash injuries, asdriver’s reaction time increases causing difficulty in: maintaining correct positions in their lanes, maintainingappropriate speeds and judging safe gaps in traffic.Descriptive study with objective of assessing knowledge, attitude and practices regarding mobile usagewhile driving amongst medical and engineering students aged 18-21 years was carried out using proformaafter taking consent.During driving, most of medical (61%, 79%) & engineering (60%, 69%) students called & receivedcalls; 55% & 60% knew it is distracted driving & only 43% & 46% always considered it as punishablerespectively. 42% & 30% read and 34% & 18% texted message; 53% & 26% used social media (WhatsApp,Facebook etc); most viewed maps/directions on their phone and felt that pedestrians using mobile are pronefor accidents. Although 87% & 88% would advice others, only 52% & 55% would restrain mobile usageduring driving respectively.This study suggest for improving on-ground situation through formal education to bring about moralresponsibility amongst youth and propose automatic electronic system in vehicles for early detection of thisglobally identified risk factor